GNSS receiver data autologging and processing - Zhang, Ruobei (2018)
Ionospheric scintillation is a phenomenon known to have many detrimental effects on the quality and integrity of signals received from global navigation satellite systems. Since it’s a common phenomenon in Singapore, this project aims to plot and model the mathematical relationship between scintillation values and time intervals. This was done by extracting, plotting and modeling the recorded GNSS data using MATLAB. Two main mathematical models for fitting were implemented: polynomial Gaussian. For 2D fitting of scintillation against local time (LT), as well as day of year (DOY), the Gaussian model was shown to be a better mathematical model for the fitting of both amplitude and phase scintillation data. For 3D fitting of scintillation against LT and DOY, a 5th degree polynomial surface in both X and Y was generated. However, this model was not able to fit the higher scintillation data recorded. Due to limitations in MATLAB, higher degree polynomial surfaces were unable to be carried out. To further improve on the quality of generated fits, further research on the methods as well as existing scintillation models is recommended